2009
DOI: 10.1002/dc.21128
|View full text |Cite
|
Sign up to set email alerts
|

Scoring system for differential diagnosis of malignant mesothelioma and reactive mesothelial cells on cytology specimens

Abstract: Cytology is the only useful tool in the detection of malignant mesothelioma (MM) at an early stage. No other methods, such as immunocytochemistry or electron microscopy, are available to distinguish MM from reactive mesothelial cells (RMC). Some objective analysis of cytology specimens is necessary. On the basis of our case review and cytological features described in previous articles, we developed a scoring system for malignant mesothelioma (SSMM) of effusion cytology to distinguish MM cells from RMC. Mesoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 15 publications
(19 reference statements)
1
17
0
Order By: Relevance
“…26 However, to achieve the differential diagnosis successfully, numerous cytomorphological parameters are required. A variety of markers, such as EMA, desmin, GLUT-1, and p53, have been reported to be useful in the discrimination of malignant mesothelioma and reactive mesothelium, but the results are not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, to achieve the differential diagnosis successfully, numerous cytomorphological parameters are required. A variety of markers, such as EMA, desmin, GLUT-1, and p53, have been reported to be useful in the discrimination of malignant mesothelioma and reactive mesothelium, but the results are not consistent.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been considered that MPM should not be diagnosed by pleural effusion cytology, since the reliable cytological criteria for the diagnosis of MPM has not been established so far and invasion cannot be assessed with specimens used in effusion fluid cytology [6,[10][11][12]. Recently, characteristic cells of MPM of epithelial type in pleural effusion have been collected and analyzed [13,14]. In addition, several molecular markers, which may assist diagnosis of early-stage MPM of epithelial type in pleural effusion cytology and histology, have been developed [15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…In normal tissues, such as liver parenchyma, a relationship between binucleated cells and cell survival was reported (Morizur et al 2010). Many cytological studies have found elevated numbers of binucleated cells in various tumors (Bollmann et al 2005;Kimura et al 2009;Minimo et al 2002;Morin et al 2000;Stelow et al 2006;Stoll et al 2011). However, binucleated cells are observed in not only malignant tumors but also normal tissues (Mizoguchi and Ishikawa 1994;Morizur et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Many cytological studies have reported that the numbers of binucleated cells were elevated in various tumors, including malignant mesothelioma, pancreatic endocrine tumor, cervical squamous lesion, angiosarcoma, and acute myeloid leukemia (Bollmann et al 2005;Kimura et al 2009;Minimo et al 2002;Morin et al 2000;Stelow et al 2006;Stoll et al 2011). However, binucleated cells are observed in not only malignant tumors but also normal tissues such as those of the heart, muscle cells, platelet progenitor-megakaryocytes, liver parenchyma, and bladder (Mizoguchi and Ishikawa 1994;Morizur et al 2010).…”
Section: Introductionmentioning
confidence: 99%